1982
DOI: 10.1139/m82-157
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of hydrogen-utilizing bacteria among N2-fixing bacteria in wetland rice roots

Abstract: Heterotrophic bacteria were isolated from wetland soil, rhizosphere soil, root and basal shoot of wetland rice, dryland soil, and root of dryland rice. The isolates were tested for N2-fixing activity and the ability to grow autotrophically under H2 + CO2 + O2. N2-fixing bacteria capable of autotrophic growth were found almost exclusively from the rhizosphere and the root of wetland rice. In another experiment, all N2-fixing bacteria isolated from wetland rice root had uptake hydrogenase activity. These finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…4B and DC, 'P. diazotrophicus' H8, P. putida GRI2-2, and P. stutzeri JM300 [36,39,46,[148][149][150]. Among them, the relation between H 2 oxidation and N 2 fixation in P. saccharophila is the best studied [148].…”
Section: H Oxidation and Chemolithotrophymentioning
confidence: 99%
See 1 more Smart Citation
“…4B and DC, 'P. diazotrophicus' H8, P. putida GRI2-2, and P. stutzeri JM300 [36,39,46,[148][149][150]. Among them, the relation between H 2 oxidation and N 2 fixation in P. saccharophila is the best studied [148].…”
Section: H Oxidation and Chemolithotrophymentioning
confidence: 99%
“…The rhizosphere could be one of these ecosystems. Watanabe et al [149] reported the predominance of H2-utilizing bacteria among N2-fixing bacteria in wetland rice roots. He-oxidizing N2-fixing bacteria could be obtained in the rhizosphere of white beans [36] by enrichment isolation.…”
Section: H Oxidation and Chemolithotrophymentioning
confidence: 99%
“…The ability to utilize hydrogen was found in A. lipoferum (70). WATANABE et al (16) reported the predominance of hydrogenutilizing bacteria among nitrogen-fixing bacteria in wetland rice roots. Since a large number of nitrogen-fixing bacteria occur around the rhizosphere of rice, hydrogenutilizing and nitrogen-fixing bacteria appear to have some relationships with rice.…”
Section: Tatmentioning
confidence: 99%
“…Watanabe et al (1982) observed predominance of H2-dependent chemolithotrophy among the diazotrophs in wetland rice soils, suggesting ecological significance of H2 assimilation for bacteria in flooded rice soils. To determine whether soybean rhizobia carrying the uptake hydrogenase, Hup(+), show any ecological advantage in their survival in flooded rice soils, pot and laboratory experiments were conducted.…”
mentioning
confidence: 79%
“…Because H2 evolves in flooded rice soils (Harrison and Aiyer 1906;Watanabe and Furusaka 1980), the H2-dependent chemolithotrophic capability of bacteria may represent an ecological advantage in flooded rice soils. Watanabe et al (1982) observed predominance of H2-dependent chemolithotrophy among the diazotrophs in wetland rice soils, suggesting ecological significance of H2 assimilation for bacteria in flooded rice soils.…”
mentioning
confidence: 99%